Geology, geochemistry and mineralogy of PGE-Cu-Ni deposits - Nadezhda Krivolutskaya (Kudos Innovations Ltd, 2021)
Magmatic deposits related to basic-ultrabasic complexes are the main source of Ni, PGE, Cr, and V in the world. Our understanding deposits’ formation contributes to the discovery of new important metals’ concentrations in the crust. Their origin is under discussion for some decades. The important problems are metal and sulfur sources and mechanism of their concentration. The Norilsk deposits located in NW Siberian traps province play key role in PGE and Ni economic. Their origin is connected with traps formation. Geology, geochemistry and mineralogy of these deposits have been studied in our projects as well as geology of other magmatic deposits. These data allowed to create a new model of the deposits' origin.